Expression of the novel maternal centrosome assembly factor Wdr8 is required for vertebrate embryonic mitoses - Inoue, Daigo; Stemmer, Manuel; Thumberger, Thomas; Ruppert, Thomas; Bärenz, Felix; Wittbrodt, Joachim; Gruss, Oliver (Nature Communications, 2017)
The assembly of the first centrosome occurs upon fertilisation when male centrioles recruit pericentriolar material (PCM) from the egg cytoplasm. The mechanisms underlying the proper assembly of centrosomes during early embryogenesis remain obscure. We identify Wdr8 as a novel maternally essential protein that is required for centrosome assembly during embryonic mitoses of medaka (Oryzias latipes). By CRISPR-Cas9-mediated knockout, maternal/zygotic Wdr8-null (m/zWdr8−/−) blastomeres exhibit severe defects in centrosome structure that lead to asymmetric division, multipolar mitotic spindles and chromosome alignment errors. Via its WD40 domains, Wdr8 interacts with the centriolar satellite protein SSX2IP. Combining targeted gene knockout and in vivo reconstitution of the maternally essential Wdr8-SSX2IP complex reveals an essential link between maternal centrosome proteins and the stability of the zygotic genome for accurate vertebrate embryogenesis. Our approach provides a way of distinguishing maternal from paternal effects in early embryos and should contribute to understanding molecular defects in human infertility., The assembly of the first centrosome occurs upon fertilisation when male centrioles recruit pericentriolar material from the egg cytoplasm. Here the authors identify Wdr8 as a maternally essential protein that is required for centrosome assembly during embryonic mitoses of medaka.